Do PESTLE Factors Impact the Development of Non-oil Manufacturing Companies in Oman? - Ammal, K. Ammani; Al Jassasi, Alanoud Rashid Nasser; AlGhafri, Sheikha (International Journal of Energy Economics and Policy, 2022)
One of the top priorities of Oman Industrial strategy 2040 is to have economic diversification and activate the role played by manufacturing sector in Oman. As the Oman public finances depend entirely on oil revenues, the development of Oman industrial sector is a key pillar of its long-term development strategy. So the present study aimed to identify and analyse the impact of PESTLE factors on the development of non-oil manufacturing companies in Oman and to suggest suitable measures to develop manufacturing companies in Oman. The researcher used both primary and secondary data for the purpose of the study. The primary data were collected through a structured questionnaire from the sample of 52 manufacturing companies of different sectors in Oman. Further, the researcher had preliminary discussions with the officials of the Department of Commerce, Industry, and Investment Promotion. The collected data were analysed with the help of appropriate statistical tools such as percentage, ANOVA, Independent Z-test, correlation, Regression, and Partial Least Square based Structure Equation Modelling. The results of the study showed that there is a positive relationship between PESTLE factors and the development of non-oil manufacturing companies in Oman.